HANDBALL AS ELECTIVE SPORT IN THE THIRD ROUND OF THE NINE YEARS PRIMARY SCHOOL - Radojica Marušić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
In the third Round of the nine years Primary school the curriculum anticipates elective subjects. One of the possible choices is the sport for the sportsman and within it are the programs for the handball. This work has proposed operational aims of the handball as the elective sport for the seventh, eight and ninth grade, which would be fulfilled through 198 classes two times a week.